Immunitet jurysdykcyjny Stolicy Apostolskiej a odpowiedzialność za nadużycia seksualne duchowieństwa. Rozważania na kanwie wyroku Europejskiego Trybunału Praw Człowieka z 12 października 2021 r. w sprawie J.C. i inni v. Belgia (Skarga nr 11625/17) - Borecki, Paweł (Studia Prawa Publicznego, 2022)
The Belgian courts and the ECtHR treating the Holy See as a state is an over-inter-pretation. The Holy See cannot be treated as a foreign sovereign. This is a historical anachronism. At the very most, we can speak of the so-called ‘spiritual sovereignty’ of the Holy See, which his related to the fact that it is the governing body of the Catholic Church. However, it has no public-law powers over church structures and its followers. The Church is a voluntary international private association of natural persons. It has no administrative power over its members. The Holy See has a superior position over bishops. Therefore, it should also be responsible for the lack of a proper reaction by these church leaders to the sexual abuse of the clergy subordinate to them. In the past, the Catholic Church operated a policy of silence (omerta) based on clericalism. The pontiﬁcate of Pope Francis brought about fun-damental changes in this area. However, the judgment of the European Court of Human Rights of October 12, 2021 is procrastinating and will probably trigger what can be termed a ‘chilling effect’. What takes precedence is the good of the inﬂuential institution – the Holy See – and not those individuals wronged in their childhood.